Displaying Tetra‐Membrane Spanning Claudins on Enveloped Virus‐Like Particles for Cancer Immunotherapy. Issue 3 (23rd November 2017) - Schneider, Irene C.; Hartmann, Jessica; Braun, Gundula; Stitz, Jörn; Klamp, Thorsten; Bihi, Mahjoub; Sahin, Ugur; Buchholz, Christian J.
Abstract : Virus‐like particles (VLPs) displaying foreign antigens have become an important tool in vaccination including the induction of immune responses against self‐antigens. Claudin 6 (CLDN6) has been identified as tumor‐associated antigen and is therefore a potential target for tumor vaccination strategies. However, as tetra‐membrane spanning protein its incorporation into VLPs while preserving a native fold is challenging. Here, we attempted the incorporation of a panel of engineered CLDN6 variants into the membrane of retrovirus‐derived VLPs. Interestingly, wild‐type CLDN6 revealed the most efficient display. VLPs presenting CLDN6 or CLDN9 derived from different donor species were produced and preservation of their native confirmation was demonstrated by antibody binding assays. VLPs displaying murine CLDN6 were used to immunize mice. Antibodies recognizing native CLDN6 as displayed on cell surfaces and mediating complement‐dependent cytotoxicity were elicited in vaccinated animals. The data suggest applications of CLDN6 displaying VLPs in cancer immunotherapy. Abstract : Claudin‐6, a tetra‐spanning transmembrane protein that is expressed in certain cancer types, is coexpressed with mouse leukemia virus (MLV) gag and pol genes to generate virus‐like particles (VLP) that display claudin‐6 on their surface membrane. These VLPs evoke claudin‐6 specific antibodies recognizing native claudin‐6 and may thus offer a novel therapeutic option in cancer immunotherapy.